24 h Levodopa–carbidopa intestinal gel may reduce falls and "unresponsive" freezing of gait in Parkinson's disease. Issue 3 (March 2015) - Chang, Florence C.F.; Tsui, David S.; Mahant, Neil; Wolfe, Nigel; Kim, Samuel D.; Ha, Ainhi D.; Drury, Melissa; Griffith, Jane M.; Fung, Victor S.C.
Abstract: Objective: We report a prospective, open label study of 24 h levodopa–carbidopa intestinal gel (LCIG) as treatment for levodopa "unresponsive" freezing of gait (FOG) associated with Parkinson's disease. Method: 5 patients with disabling FOG, documented as being levodopa "unresponsive", were commenced on continuous 24 h infusion LCIG therapy with the night-time rate at 50–80% of the daytime infusion rate. Patients underwent baseline, 3 and 6 month gait assessments, documentation of their falls frequency and completed FOG questionnaires. Result: Median 360° turn time improved by 54%, fall frequency score reduced from 3 to 0 at 6 months, FOG questionnaire score improved by 14% and Timed Up- and -Go 8 m walk was unchanged. Conclusion: 24 h LCIG therapy may reduce levodopa "unresponsive" FOG and associated falls. A larger prospective study is needed for confirmation. Highlights: We report a prospective 24 h LCIG infusion as treatment for "unresponsive" FOG in PD. Median 360° turn time improved by 54%, fall frequency reduced at 6 months. 24 h LCIG therapy may reduce levodopa "unresponsive" FOG and associated falls.